Creation and testing of the Domiscore-a tool to characterize the impact of housing on health and well-being - Aude Richard; Camille Bruat; Didier Febvrel; Fabien Squinazi; Jean Simos; Denis Zmirou-Navier; the members of the HCSP working group (BMC, 2023)
Abstract Background Despite evidence of the major impact housing carries on health, many individuals still live in unhealthy dwellings. In France, the Domiscore has been proposed as a tool to assess the quality of dwellings with regard to their health impact, to allow for a better detection of unsafe housing and to improve dwellings. The aim of this paper is to present the method used to construct the Domiscore and test its relevance and usability. Methods The Domiscore grid, inspired by the Nutriscore, consists of 46 variables-such as air quality, light or outdoor view. Each variable is scored on a four-point scale using in situ observation, mandatory diagnostics and open access data. The sum of each variable's score results in an overall risk score for the dwelling. The Domiscore was tested in two phases. During the first testing phase, 11 real estate professionals, health professionals and social workers used the Domiscore for on-site visits in different geographic areas of France. They then participated in a semi-structured qualitative interview. The second phase consisted in a public consultation with diverse stakeholders such as public authorities, housing activists and social workers, using an online survey to collect their opinions on the Domiscore's relevance, understandability and usability. Results The Domiscore was tested on 28 homes. Variables completion rates were high irrespective of tester profile for all home visits (91%, SD = 4.7%). The mean time needed to fill in the grid was 1.5 h. The public consultation returned 151 responses. The Domiscore was deemed easy to understand, relevant, and rather easy to fill out. Most participants found the Domiscore useful for information gathering, awareness raising, detecting at-risk situations and agreed that it could contribute to enhance housing conditions. Its length was noted, although the inclusion of additional variables was also suggested. Conclusions The results of this study suggest that the Domiscore is accessible to housing specialists and other professionals for the evaluation of a dwelling's health impacts and the standardized detection of dangerous situations. The testing process allowed for improvements in the grid and training materials for future users.